Penggunaan Gimkit sebagai Media Belajar Digital untuk Meningkatkan Penguasaan Kosakata Siswa Kelas VII SMPN 2 Kisaran - Saputra, Erlangga; Rahma Yunita Ansi; Endang Dorisday Sitorus (ELP (Journal of English Language Pedagogy), 2025)
Vocabulary retention is a persistent challenge for beginner EFL learners. This classroom action research investigated the effectiveness of Gimkit, a digital game-based learning tool, in improving vocabulary mastery among seventh-grade students at UPTD SMPN 2 Kisaran. The study was conducted over two action-research cycles based on the Kemmis and McTaggart (1988) model and involved 32 students from class VII-9 who had low initial vocabulary scores. Data were gathered through vocabulary tests and student interviews. The results demonstrated a notable improvement in mastery: only 18.75% of students passed the minimum criterion in the pre-test, which increased to 46.87% in Cycle 1 and 90.6% in Cycle 2. The integration of visual aids and the use of Gimkit’s rematch feature in Cycle 2 enhanced student engagement and memory retention. Interviews indicated that students found the learning process more enjoyable and motivating. Nonetheless, some learners continued to experience difficulties in vocabulary retention due to external factors such as health issues and personal challenges. These findings highlight the potential of Gimkit as an effective and engaging digital tool to support vocabulary acquisition in EFL classrooms, particularly at the beginner level.